2003
DOI: 10.1074/jbc.m306410200
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of GATA-1 Binding to DNA

Abstract: Mammalian GATA transcription factors are expressed in various tissues in a temporally regulated manner. The prototypic member, GATA-1, is required for normal erythroid, megakaryocytic, and mast cell development. This family of DNA-binding proteins recognizes a consensus (A/T)GATA(A/G) motif and possesses homologous DNA binding domains consisting of two zinc fingers. The C-terminal finger of GATA-1 recognizes the consensus motif with nanomolar affinities, whereas the N-terminal finger shows a binding preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Furthermore, it has been shown that the tail sequence QTRNRK in the C-finger of GATA-1 is important for determining the sequence specificity of this domain (39). However, inspection of the structure of the GATA-1⅐DNA complex indicates that five of the six side chains do not appear to make any significant contacts with the minor groove.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that the tail sequence QTRNRK in the C-finger of GATA-1 is important for determining the sequence specificity of this domain (39). However, inspection of the structure of the GATA-1⅐DNA complex indicates that five of the six side chains do not appear to make any significant contacts with the minor groove.…”
Section: Discussionmentioning
confidence: 99%
“…(2) The disassociate rate of GATA-1 binding to its DNA promoter is K d = 2.8 nM, which is more stable than the binding of GATA-2 to its promoter site K d = 4.4 nM [42]. In addition, the disassociate rate of PU.1 binding to its DNA promoter is K d = 170 nM [43].…”
Section: Methodsmentioning
confidence: 99%
“…The synergistic effect of PU.1 on GATA-1-mediated transactivation could potentially be mediated by a conformational change in GATA-1 when it binds to the two tandem GATA sites present in the MBP-P2 promoter. It was reported recently that the ability of GATA-1 to mediate transactivation can be modified by its DNA binding target sequences, such that high affinity tandem and/or palindromic GATA-binding sites found in several different genes including the ⑀-globin silencer (90) and testis GATA-1 promoter of rats and mice (91) may either promote or interfere with GATA-1 transactivating activity (90,92). Only the C-terminal zinc finger of GATA-1 is capable of independently binding to a GATA consensus site and stimulating transcription, whereas the N-terminal finger shows no independent DNA binding activity but can modify binding specificity (stabilize or disrupt binding) at some naturally occurring dual GATA sites that have been shown to be critical for gene expression (93)(94)(95)(96)(97).…”
Section: Discussionmentioning
confidence: 99%